If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -3) = -18x Reorder the terms: 9(-3 + x) = -18x (-3 * 9 + x * 9) = -18x (-27 + 9x) = -18x Solving -27 + 9x = -18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18x' to each side of the equation. -27 + 9x + 18x = -18x + 18x Combine like terms: 9x + 18x = 27x -27 + 27x = -18x + 18x Combine like terms: -18x + 18x = 0 -27 + 27x = 0 Add '27' to each side of the equation. -27 + 27 + 27x = 0 + 27 Combine like terms: -27 + 27 = 0 0 + 27x = 0 + 27 27x = 0 + 27 Combine like terms: 0 + 27 = 27 27x = 27 Divide each side by '27'. x = 1 Simplifying x = 1
| 230p-1010=650p-400-p | | 8t+6t-12t=16 | | 5u-2u+2=11 | | 5(2k-1)=32 | | -9g-4g+9g+-7g+2g=18 | | 2.3p-10.1=6.49-4 | | 30-(3x+4)=(x+7)+x | | 6(3x-7)=6x-6 | | 3x+2x+1+5x=180 | | 6n-20n+17n=-18 | | 2.3p-10.1=6.4-4 | | -32=10+6r | | 4(J+8)=54 | | 10k-10k+5k-2k=18 | | 2.3p-10.1=6.5p-4-0.01 | | -11-3m=16 | | -15t+-18t-2t+12t+11t=12 | | 6v+16=3v+16 | | 2x-y+z=7 | | -9+4x=21 | | 4s+5s=27 | | X^2=-8x-5 | | 6h-2h=16 | | 2(h-3)=8 | | 12w-2w=10 | | 20=7y+6 | | 7k+k=16 | | 10x-8x=20 | | 15(24-2x)=15x | | 8(4x-1)-32= | | 1x+.125+.75x=.66+5x | | 1.4n+2=2n+3.2 |